Is money neutral in stock markets? the case of Malaysia. - Puah, Chin Hong; Habibullah, Muzafar Shah; Liew, Venus Khim Sen (Economics Bulletin, 2010)

(untitled)
The objective of this study is to examine whether the notion of monetary neutrality holds in Malaysian stock market. Our findings indicate that there is considerable evidence against the long-run neutrality (LRN) of money in Malaysian stock market. The important implication is that the stock market is inefficient with respect to money supply. Agents might have the opportunity to gain excess profit from the stock market using the information on changes in the stock of money to predict the movements in stock indexes.